2013
DOI: 10.1002/jctb.4158
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mycobacterium sp. strain Spyr1 biomass and its biosorption behavior towards Cr(III) and Cr(VI) in single, binary and multi‐ion aqueous systems

Abstract: BACKGROUND: Mycobacterium sp. biomass was used for removal of Cr(III) and Cr(VI) species from aqueous systems. Experimental results were processed with different kinetic, isotherm and thermodynamic models. Studies of the effect of co-ions, biomass characterization and desorption were also undertaken. RESULTS: Cr(III) and Cr(VI) sorption on Mycobacterium sp. biomass followed Ho pseudo-second-order kinetics. The Langmuir isotherm model described the biosorption of both chromium species, whereas the Temkin isothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The low R 2 values at different temperatures showed that this model can not be applied to predict the biosorption kinetics. However, Cr(VI) biosorption may be proceeded with physisorption mechanism [12].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The low R 2 values at different temperatures showed that this model can not be applied to predict the biosorption kinetics. However, Cr(VI) biosorption may be proceeded with physisorption mechanism [12].…”
Section: Resultsmentioning
confidence: 99%
“…The fitness of Cr(VI) biosorption data with low correlation coefficients as well as lower Q e,cal comparison to Q e,exp indicated that Cr(VI) biosorption on Eupatorium adenophorum- alginate beads did not follow Lagergren pseudo-first order reaction [12].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations